Perceptions and Implications of Principals' Instructional Leadership Practices - Gift Muyunda (Cita Konsultindo Research Center, 2022)
The leadership practice of the principal is known to be a key factor in supporting the teaching and learning process, but how that leadership is experienced and instructionally enacted by teachers is much less clear. The purpose of this article was to explore Principal instructional leadership practices, its conceptualization and how principals perceive and ratify their role as instructional leaders in secondary schools of Zambia. A qualitative study method was chosen, and in-depth interviews were used to obtain in-depth information from the participants. The study sample involved 47 principals composed of 25 principals from public secondary schools and 22 principals from private secondary schools using purposive sampling technique. Data was analyzed inductively and successively coded to generate themes. The findings of the study show that principals understood and defined tasks concerning cultivate instructional practice. Precisely, concerning supervision of teachers, how the monitored and evaluated the excellence of teaching and knowledge in their instructions. The findings also indicate that there is strong policy expectance, delineated in the Zambian National Education Policy 1996 that principals are responsible and accountable for the overall school improvement and supposed to be instructional leaders. The findings of this study shows that principals in Zambia practice instructional leadership in their leadership roles. The paper concludes with suggestions for future directions for instructional leadership practice in Zambia to increase the knowledge regarding instructional leadership movement in developing countries like Zambia in the African context.